2016
DOI: 10.5897/ajb2015.14974
|View full text |Cite
|
Sign up to set email alerts
|

A review of cashew (Anacardiumoccidentale L.) apple: Effects of processing techniques, properties and quality of juice

Abstract: A review including the processing techniques, properties and uses of cashew apple juice is reported. Cashew apple has multipurpose ; it can be processed to obtain human food. The process of cashew apple into several by-products can affect its nutritional, microbiological, and sensorial quality attributes. Therefore, clarification methods, thermal treatment and high hydrostatic pressure modify nutritional, microbiological, and sensorial attributes of cashew apple products. Moreover, the storage stability of cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 57 publications
(87 reference statements)
1
15
0
Order By: Relevance
“…However, the pseudo-fruits are richer in the antioxidant compounds only at the initial stage of maturity (Table 1, AAC, and PC values). The authors reported that the anthocyanins, total carotenoids, TSS, TSS/TA, polymeric tannins, vitamin C, and reducing sugars increase continuously during the maturation of the cashew apples (Makanjuola et al, 2013;Dedehou et al, 2016;Das and Arora 2017). These results are proof of the behavior of the samples in this study, since values increased from day 0 to day 6 and later on, decreased on days 9 to 12.…”
Section: Color and Chemical Correlationsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the pseudo-fruits are richer in the antioxidant compounds only at the initial stage of maturity (Table 1, AAC, and PC values). The authors reported that the anthocyanins, total carotenoids, TSS, TSS/TA, polymeric tannins, vitamin C, and reducing sugars increase continuously during the maturation of the cashew apples (Makanjuola et al, 2013;Dedehou et al, 2016;Das and Arora 2017). These results are proof of the behavior of the samples in this study, since values increased from day 0 to day 6 and later on, decreased on days 9 to 12.…”
Section: Color and Chemical Correlationsupporting
confidence: 82%
“…T he cashew (Anacardium occidentale L.) is a product with a high content of flavors, colors, and the presence of fructose as the predominant sugar. It is cultivated in different parts of the world (Makanjuola et al, 2013;Dedehou et al, 2016) and in some Latin American countries, including Venezuela where it grows wild and without a protocol of cultivation (Guerrero and Velazquez-Moreira 2014;Guerrero et al, 2019). These fruits represent an important part of the production of cashew nuts (fruit) but cashew apple is non-used in the food industry after the extraction of juice (Da Costa et al, 2009).…”
mentioning
confidence: 99%
“…Cashew apples are also abundant in minerals including iron (30 times higher than lemon), calcium, and phosphorus and contain other nutrients in high quantities including about 9% protein, 4% lipid, 8% cellulose, and 1% pectin (Das & Arora, 2017). However, the high content of tannin (around 0.2%‒0.5%) is responsible for the acrid and bitter taste of the fruit, discouraging its consumption and thus causing difficulties in processing into palatable products (Assis et al, 2007; Emmanuelle et al., 2016). Therefore, cashew apple is often discarded after harvest or used as fertilizers, narrowing the economic value of the cashew industry and contributing to the accumulation of agricultural waste.…”
Section: Introductionmentioning
confidence: 99%
“…One that has a bright prospect is cashew apple juice. This is because the cashew apple is juicy with a moisture content of 86.3 g 100 g -1 [2] and rich in vitamin C which is 180 mg 100 g -1 [2] and 126 mg 100 mL -1 to 372 mg 100 mL -1 [3] three to six times more vitamin C than orange juice [4], and as a very good source of antioxidants [5].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of tannin in food and drinks can have a positive and negative effect on those who consume it. The negative effects are, i) can reduce the nutritional value of macromolecules (protein, amino acids, carbohydrates, sugars), micromolecules (vitamins, minerals) and their bioavailability [5,8]. ii) negative effect to digestive [9] by forming insoluble complexes, thereby increasing levels of nitrogenous stool, which can inhibit the growth of experimental animals including rats.…”
Section: Introductionmentioning
confidence: 99%